Incidence and Risk Factors for Retinal Detachment and Retinal Tear after Cataract Surgery - Michael J. Morano, MD; M. Ali Khan, MD; Qiang Zhang, PhD; Colleen P. Halfpenny, MD; Douglas M. Wisner, MD; James Sharpe, MS; Alexander Li, MS; Maurizio Tomaiuolo, PhD; Julia A. Haller, MD; Leslie Hyman, PhD; Allen C. Ho, MD; Aaron Y. Lee, MD, MSCI; et al. (Ophthalmology Science, 2023)
Objective: To report the incidence of and evaluate demographic, ocular comorbidities, and intraoperative factors for rhegmatogenous retinal detachment (RRD) and retinal tear (RT) after cataract surgery in the American Academy of Ophthalmology IRIS® Registry (Intelligent Research in Sight). Design: Retrospective cohort study. Participants: Patients aged ≥ 40 years who underwent cataract surgery between 2014 and 2017. Methods: Multivariable logistic regression was used to evaluate demographic, comorbidity, and intraoperative factors associated with RRD and RT after cataract surgery. Main Outcome Measures: Incidence and risk factors for RRD or RT within 1 year of cataract surgery. Results: Of the 3 177 195 eyes of 1 983 712 patients included, 6690 (0.21%) developed RRD and 5489 (0.17%) developed RT without RRD within 1 year after cataract surgery. Multivariable logistic regression odds ratios (ORs) showed increased risk of RRD and RT, respectively, among men (OR 3.15; 95% confidence interval [CI], 2.99–3.32; P < 0.001 and 1.79; 95% CI, 1.70–1.89; P < 0.001), and younger ages compared with patients aged > 70, peaking at age 40 to 50 for RRD (8.61; 95% CI, 7.74–9.58; P < 0.001) and age 50 to 60 for RT (2.74; 95% CI, 2.52–2.98; P < 0.001). Increased odds of RRD were observed for procedure eyes with lattice degeneration (LD) (10.53; 95% CI, 9.82–11.28; P < 0.001), hypermature cataract (1.61; 95% CI, 1.06–2.45; P = 0.03), complex cataract surgery (1.52; 95% CI, 1.4–1.66; P < 0.001), posterior vitreous detachment (PVD) (1.24; 95% CI, 1.15–1.34; P < 0.001), and high myopia (1.2; 95% CI, 1.14–1.27; P < 0.001). Lattice degeneration conferred the highest odds of RT (43.86; 95% CI, 41.39–46.49; P < 0.001). Conclusion: In the IRIS Registry, RRD occurs in approximately 1 in 500 cataract surgeries in patients aged > 40 years within 1 year of surgery. The presence of LD conferred the highest odds for RRD and RT after surgery. Additional risk factors for RRD included male gender, younger age, hypermature cataract, PVD, and high myopia. These data may be useful during the informed consent process for cataract surgery and help identify patients at a higher risk of retinal complications. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.